Usulan Perbaikan Penilaian Kinerja Operator Produksi Menggunakan Metode Balance Scorecard Berdasarkan KPI di PT. Meidoh Indonesia - Azizah, Rosida; Sari, Rianita Puspa; Savariyani, Eva (Universitas Indraprasta PGRI Jakarta, 2025)
Based on the results of the observation, it was found that there is no definite benchmark for employee performance evaluation, especially in the production department at PT Meidoh Indonesia. Therefore, this research aims to identify and design performance assessments in the production department of PT Meidoh Indonesia. The method used is the Balance Scorecard method based on Key Performance Indicators (KPI). Essentially, the use of the balance scorecard method has 4 perspectives that will be structured into Key Performance Indicators (KPI). The result in this research, only 3 perspectives are used according to the company's conditions at that time. These 3 perspectives consist of the financial perspective with the Key Performance Indicator (KPI) of reducing purchases and production costs, the customer perspective with the Key Performance Indicator (KPI) of reducing the delay process, and the internal process perspective of improving workforce productivity, reducing scrap, and eliminating abnormal occurrences.